2017
DOI: 10.1016/j.canlet.2017.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Plac8 promotes pro-survival function of autophagy in cadmium-induced prostate carcinogenesis

Abstract: Chronic exposure to cadmium is known to be a risk factor for human prostate cancer. Despite over-whelming evidence of cadmium causing carcinogenicity in humans, the specific underlying molecular mechanisms that govern metal-induced cellular transformation remain unclear. Acute exposure (up to 72 h) to cadmium induces apoptosis in normal prostate epithelial cells (RWPE-1), while chronic exposure (>1 year) transforms these cells to a malignant phenotype (cadmium-transformed prostate epithelial cells; CTPE). Incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 46 publications
3
29
0
Order By: Relevance
“…We previously demonstrated the implantation of Cdtransformed RWPE-1 cells; these cells formed tumors in xenograft models 33,34 . Similarly, this study helped show that chronic exposure to Cd resulted in malignant transformation of BPH1 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously demonstrated the implantation of Cdtransformed RWPE-1 cells; these cells formed tumors in xenograft models 33,34 . Similarly, this study helped show that chronic exposure to Cd resulted in malignant transformation of BPH1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, this study helped show that chronic exposure to Cd resulted in malignant transformation of BPH1 cells. We previously showed that defective autophagy was responsible for Cd-induced transformation of RWPE-1 33,35 . Here, ZIC2 and GLI1 is responsible for Cd-inducted transformation in BPH1 cells, and it appears that it is specific to BPH1 cells and not to normal prostate epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found enhanced autophagy in PLAC8-THP-1 cells. Recent studies demonstrated that PLAC8 is a critical regulator of autophagy in pancreatic cancer cell lines and prostate epithelial cells (48,49). Whereas the mechanisms of action of PLAC8 in autophagy are not clear at present, it was possible that PLAC8 regulates the autophagic machinery by facilitating autophagosome-lysosome fusion.…”
Section: Discussionmentioning
confidence: 99%
“…From our two previously published studies, PLAC8 was relatively highly expressed in lung cancer and breast cancer tissues, and contributed to cancer progression [12,13]. A number of studies have demonstrated a role of PLAC8 in in the regulation of autophagy during pancreatic cancer progression and prostate carcinogenesis [14,15].…”
Section: Backgroudmentioning
confidence: 98%
“…The sensitivity changes were explored by using MTS and colony formation assays. We here confirmed that MCF7/ADM PLAC8 silencing group become more sensitive to ADM than the control group ( Figure. PLAC8 modulates ADM resistance and autophagy through p62 participation PLAC8 has been shown to promote autophagosome lysosome fusion by activating pro-survival function of autophagy in pancreatic cancer [14,15]. We then assessed PLAC8 regulation to autophagy in breast cancer cells.…”
Section: Intrinsically and Acquired Adm-resistance In Breast Cancer Cmentioning
confidence: 99%